Study of Kinetics of Silver with Tetra(p-carboxyphenyl)porphyrin - Rahimi, Rahmatollah; Moharrami, Fariba (Asian Journal of Chemistry, 2010)
The kinetics formation of labile complex Ag(I) tetra(p-carboxy-phenyl)porphyrin (TCPP) was investigated at 25 ºC and I = 0.1 M (NaNO3). By spectrophotometric titration, the composition ratio of the complex was established to be 2:1 (Ag:H2TCPP). The equilibrium constant (K) was found to be log 10-6.53. Binding of the first Ag(I) was found to be rate determining step with rate constant, k1 = 4.67 × 102. A plausible mechanism is discussed.